PERANCANGAN SISTEM MONITORING EVACUATED TUBE SOLAR DRYER STUDI KASUS PROSES PENGERINGAN RUMPUT LAUT - Prasetyo, Teguh; Irawan, Ibnu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research applies the simples moving average (SMA) method with period of 5 and 10 to filter monitoring data from solar drying system using an evacuated tube collector. Data filtering was used to eliminate measurement noise. Data was collected at five-minutes intervals. These SMA periods were also suitable for measuring humidity both in the environment and inside the drying cabinet. However, for temperature measurements inside the drying cabinet, only the 5-period SMA method could be used, as applying a 10-period SMA resulted in deviations exceeding the specified accuracy limits. In contrast, the monitoring of seaweed mass data did not required the use of SMA method, since its application led to significant measurement deviation from the actual values.